2017
DOI: 10.17512/ios.2017.2.6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biomass (Chlorella vulgaris, Scenedesmus armatus) Concentrations on Zn 2+ , Pb 2+ and Cd 2+ Biosorption from Zinc Smelting Wastewater

Abstract: Non-modified and chemically modified algal biomass of Chlorella vulgaris and Scenedesmus armatus were chosen to examine their Zn 2+ , Pb 2+ and Cd 2+ sorption activity. The dry biomass was chemically modified with 1M HNO3 in order to determine the influence of acid--treatment on the heavy metal ions removal rate. The heavy metal uptake process was found to be rapid and very efficient. The sorption process of heavy metals is highly pH-dependent. It influences heavy metal forms in the solution, and functional gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Biosorption can be applied using different dry biomass types to remove metals in wastewater [ 47 ]. Microalgae cells have the potential to be utilized for heavy metal removal due to their ability to accumulate Hg, Cd, Zn, Au, Ag, Co, Mn, Cs, Ni, Fe, Cu, and Cr in their cells [ 44 , 48 ]. In addition, toxic metals such as Ni and Al can be removed from industrial wastewater by Spirulina platensis and Chlorella vulgaris strain.…”
Section: Wastewater and Water Treatmentmentioning
confidence: 99%
“…Biosorption can be applied using different dry biomass types to remove metals in wastewater [ 47 ]. Microalgae cells have the potential to be utilized for heavy metal removal due to their ability to accumulate Hg, Cd, Zn, Au, Ag, Co, Mn, Cs, Ni, Fe, Cu, and Cr in their cells [ 44 , 48 ]. In addition, toxic metals such as Ni and Al can be removed from industrial wastewater by Spirulina platensis and Chlorella vulgaris strain.…”
Section: Wastewater and Water Treatmentmentioning
confidence: 99%
“…By increasing the metal ion concentration, the biosorption process is reduced the competitive dispersion of metal ions has risen at the sites available on the adsorbent surface at high concentrations; these pores are closed, and metal ions are prevented from going deep into the absorbent pores, implying that adsorption occurs exclusively on the surface, Putri and colleagues concluded that decline in adsorption, indicating saturation of all the binding sites on the algal surface [22]. The maximum adsorption capacities of Scenedesmus armatus and Chlorell avululgaris against zinc, Pb +2 , and Cd +2 ions were demonstrated by Zabochnicka-Witek and Ryga at the lowest sorbent concentrations [23]. pH is one of the most important parameters influencing the rate and strength of the initial adsorption.…”
Section: Effect Of Cu +2 Ion Concentrations and Ph On The Adsorption ...mentioning
confidence: 99%
“…Biomasa roślin wodnych, jak np. biomasa mikroglonów, może być z powodzeniem wykorzystywana do produkcji biopaliw ciekłych (biodiesel, bioetanol) lub gazowych (biogaz, biowodór), bądź może stanowić paliwo stałe wykorzystywane bezpośrednio do spalania [Zabochnicka-Świątek, Rygał 2017]. Kaloryczność lądowej biomasy roślinnej wynosi od 14 do 19 MJ/kg [Chrapka 2008], a kaloryczność biomasy mikroglonów jest wyższa i wynosi od 18 do 21 MJ/kg [Bei i in.…”
Section: Wstępunclassified